From health behaviours to health practices : critical perspectives - Cohn, Simon (Chichester, West Sussex ; Malden, MA : John Wiley/Blackwell, 2014)
"Presents a collection of international contributions that complement, as well as critique, dominant conceptualisations of health behaviour"--Provided by publisher.
1. From health behaviours to health practices: an introduction / Simon Cohn -- 2. Actors, patients and agency: a recent history / David Armstrong -- 3. A socially situated approach to inform ways to improve health and wellbeing / Christine Horrocks and Sally Johnson -- 4. A relational approach to health practices: towards transcending the agency-structure divide / Gerry Veenstra and Patrick John Burnett -- 5. Environmental justice and health practices: understanding how health inequities arise at the local level / Katherine L. Frohlich and Thomas Abel -- 6. Why behavioural health promotion endures despite its failure to reduce health inequities / Fran Baum and Matthew Fisher -- 7. Behaviour change and social blinkers? The role of sociology in trials of self-management behaviour in chronic conditions / Bie Nio Ong, Anne Rogers, Anne Kennedy, Peter Bower, Tom Sanders, Andrew Morden, Sudeh Cheraghi-Sohi, Jane C. Richardson and Fiona Stevenson -- 8. Thinking about changing mobility practices: how a social practice approach can help / Sarah Nettleton and Judith Green -- 9. Providers' constructions of pregnant and early parenting women who use substances / Cecilia Benoit, Camille Stengel, Lenora Marcellus, Helga Hallgrimsdottir, John Anderson, Karen MacKinnon, Rachel Phillips, Pilar Zazueta and Sinead Charbonneau -- 10. Staying 'in the zone' but not passing the 'point of no return': embodiment, gender and drinking in mid-life / Antonia C. Lyons, Carol Emslie and Kate Hunt -- 11. Complexities and contingencies conceptualised: towards a model of reproductive navigation / Erica van der Sijpt -- 12. Sustained multiplicity in everyday cholesterol reduction: repertoires and practices in talk about 'healthy living' / Catherine M. Will and Kate Weiner -- 13. Enjoy your food: on losing weight and taking pleasure / Else Vogel and Annemarie Mol.
"Originally published as Sociology of health & illness ; v. 36, issue 2."
Machine generated contents note: Notes on ContributorsFrom health behaviours to health practices: an introduction (Simon Cohn)Actors, patients and agency: a recent history (David Armstrong)A socially situated approach to inform ways to improve health and wellbeing (Christine Horrocks and Sally Johnson)A relational approach to health practices: towards transcending the agency-structure divide (Gerry Veenstra and Patrick John Burnett)Environmental justice and health practices: understanding how health inequities arise at the local level (Katherine L. Frohlich and Thomas Abel)Why behavioural health promotion endures despite its failure to reduce health inequities (Fran Baum and Matthew Fisher)Behaviour change and social blinkers? The role of sociology in trials of self-management behaviour in chronic conditions (Bie Nio Ong, Anne Rogers, Anne Kennedy, Peter Bower, Tom Sanders, Andrew Morden, Sudeh Cheraghi-Sohi, Jane C. Richardson and Fiona Stevenson)Thinking about changing mobility practices: how a social practice approach can help (Sarah Nettleton and Judith Green)Providers' constructions of pregnant and early parenting women who use substances (Cecilia Benoit, Camille Stengel, Lenora Marcellus, Helga Hallgrimsdottir, John Anderson, Karen MacKinnon, Rachel Phillips, Pilar Zazueta and Sinead Charbonneau)Staying 'in the zone' but not passing the 'point of no return': embodiment, gender and drinking in mid-life (Antonia C. Lyons, Carol Emslie and Kate Hunt)Complexities and contingencies conceptualised: towards a model of reproductive navigation (Erica van der Sijpt)Sustained multiplicity in everyday cholesterol reduction: repertoires and practices in talk about 'healthy living' (Catherine M. Will and Kate Weiner)Enjoy your food: on losing weight and taking pleasure (Else Vogel and Annemarie Mol)Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Social medicine; Diseases -- Social aspects; Health Behavior; Sociology, Medical; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Diseases -- Social aspects; Social medicine; Collected Works; Electronic books